Thermophysical Characterization of Ceramic Synthesized from Rice Husk Ash and Erbium Oxide - Mohd. Mustapha, Haslinawati (2010)
In this study, the chemical contents of rice husk (RH) were determined using Inductive Couple Plasma (ICP). Various types of acid were used in the leaching process of the RH samples. ICP data shows that, samples that have undergone acid leaching contained a lower percentage of metallic elements compared to untreated sample. Hydrochloric acid (HCl) leaching of husk is superior to Sulfuric acid (H2SO4) and Nitric acid (HNO3) for removing the metallic elements. It also contained more percentage of silica (SiO2) which is 94.61%, treated with HNO3 (93.71%), treated with H2SO4 (92.56%) and for untreated (85.48%). For heat treatment, the required combustion temperature is 500 °C and above to produce white ash within a reasonable time (~1 hour in this study). By heat treating rice husk ash (RHA) at 800 °C for 2 hours, all the carbon contained in RHA (black ash) was removed and an amorphous white rice husk ash (WRHA) is produced. The weight loss of RHA sample treated at 500 °C was found to be about 80.71% and it was increased to 88.64% after treatment at 800 °C. Ceramics produced from WRHA and Erbium Oxide (Er2O3) was made by mixing, milling, grinding, pressing and sintering procedure. They were well analyzed by XRD, scanning electron microscopy (SEM) and energy dispersive x-ray (EDX), fourier transform infrared (FTIR) and laser flash apparatus (LFA). The XRD revealed the changes in crystal phase due to sintering temperature. Cristobalite and trydimite phase were observed from all compositions. While for sample with addition of 10% and 20% of Er2O3, Er2O3 and Er2O7Si2 phase were observed as well as cristobalite and trydimite phase. SEM is useful tool to analyze structural changes that occur at the surface of ceramics. The morphology analysis of samples showed that the microstructures of samples are related to the phase of the crystal. On the other hand, EDX analysis confirm the composition of elements contain in the samples. FTIR analysis showed the chemical group presents in the samples. The main band is observed as Si-O-Si stretching band in all samples due to its silica composition. Laser flash system was used to measure thermal diffusivity in order to compare the structural of samples with their thermal features. It was shown that thermal diffusivity is increased as sintering temperature increased. Changes in crystal phase as proved by XRD (from cristobalite to tridymite and Er2O3 to cristobalite and tridymite) are closely followed by thermal diffusivity. Thermal diffusivity is also dominated by their microstructure, density and temperature.